PRELIMINARY OUTCOMES OF FEASIBILITY AND EFFICACY OF BRIEF RESILIENCE STRESS TRAINING: A PILOT STUDY OF THE MARST PROGRAM - Aileen M. Pidgeon; Andrew Hanna; Lenard W. Pidgeon; Amelia-Rose Read; Frances Klaassen (European Scientific Journal, ESJ, 2015)
Human service professionals are at risk for stress-related psychological problems. Whilst there has been considerable research of the causes and effects of these problems, little research has been conducted on brief interventions to cultivate resilience in this at risk occupational group. Mindfulness-based interventions, which have shown promise in cultivating resilience, are also widely accepted as efficacious in the treatment of psychological disorders. The aims of this paper were to gather preliminary information regarding the feasibility of implementing a brief Mindful Awareness Resilience Skills Training program (MARST) to enhance resilience, mindfulness and positive emotions in human service professionals. The program consisted of resilience and mindfulness enhancement strategies. Twenty-two participants completed the two x oneday group training sessions over two weeks. Data were analyzed using repeated measures analysis of variance, which indicated a significant main effect of intervention. Post hoc analysis showed significant improvements between pre and post intervention scores on measures of resilience (p = .02) mindfulness (p < .001), positive reappraisal (p = .01) and positive emotions (p = .03). When comparisons were made between pre-MARST and one month follow up, positive effects of intervention were found on the measures of resilience (p < .001), mindfulness (p < .001), positive reappraisal (p < .001) and the reduction of negative emotions (p = .02). The participants provided positive feedback on the content and delivery of the MARST program. The results from this study provide preliminary support for the MARST program to enhance resilience, mindfulness, positive reappraisal and positive emotions and amongst human service professionals.